The relationship between adolescent injuries and risk factors - Z. V. Lashkul; V. V. Chemirisov; V. L. Kurochka; N. Y. Motovytsya; L. D. Yarova (Сучасні медичні технології)
Purpose of the study. The aim of our study was to examine the relationship between existing risk factors and adolescent trauma